In‐situ Raman monitoring of the poly(vinylidene fluoride) crystalline structure during a melt‐spinning process. (20th February 2021) - Chapron, David; Rault, François; Talbourdet, Anaëlle; Lemort, Guillaume; Cochrane, Cédric; Bourson, Patrice; Devaux, Eric; Campagne, Christine
Abstract: Poly(vinylidene fluoride) (PVDF) fibres used to develop sensors or energy harvesters have great potential in the sector of portable electronic devices and especially in the development of smart textiles. This polymorphic polymer is known for several years for its excellent piezoelectric properties related to its different crystalline phases and more particularly to the polar β‐phase is the subject of studies dedicated to the development, optimization, and characterization of β‐PVDF fibres. The presence and the evolution of the different crystalline phases are linked to different factors and can be controlled for example by changing some parameters during the process. In the case of the spinning process, the influence of the operating conditions, such as temperature and drawing on the crystalline structure is currently determined by post‐mortem analyses. Development of 'mimetic' tests to characterize in situ the evolution of the crystalline structure of a mechanically stretched polymer is a possible way. Nevertheless, this cannot totally reproduce a real process. For the first time, phase transformations and evolutions of PVDF during a melt‐spinning process were studied online thanks to in situ Raman spectroscopy measurements. Performed at different stages of the spinning line, this method allows us to follow the evolution of the crystalline phases in real time, during the key steps of the process and to conclude on the conditions for obtaining the piezoelectric phase. The successful online characterization of PVDF crystalline phases by Raman spectroscopy opens new perspectives for the optimization of these fibres by controlling the evolution of the structure when changing process parameters. Abstract : The crystalline phases of PVDF fibres have been monitored during a melt‐spinning process on a pilot using a Raman probe as optical sensor. This work shows the potential of Raman spectroscopy for online monitoring of textile fibres production processes throughout shaping. The influence of process parameters and the location of where structural changes take place are discussed.